Green consumer segmentation: managerial and environmental implications from the perspective of business strategies and practices - Afonso, Carolina (2018)
With the new millennium, environmental concern entered a new phase, with stricter governmental regulations and incentives. Currently, within environmental issues, there is a broader challenge to commitment with economic and social goals. This is motivating companies and organizations to participate in transformation processes with the aim of minimizing the negative impacts of their activities. Within this context, new business philosophies, emerged empowering organizations to consider sustainability issues that have come to be viewed as an innovative and differentiating factor, providing competitive advantages (Fraj-Andres, MartinezSalinas, & Matute-Vallejo. Journal of Business Ethics, 88,263-286, 2009; Leipziger. The corporate responsibility code book. Greenleaf Publishing Limited, 2016; Leipziger. The corporate responsibility code book. Greenleaf Publishing Limited, 2016). Therefore, organizations have begun incorporating these concerns in their processes, adopting green management policies, and including green marketing strategies in order to remain competitive (Straughan & Roberts. Journal of Consumer Marketing, 16(6), 558-575, 1999; Rivera-Camino. European Journal of Marketing, 41, 1328-1358, 2007). From the marketing perspective, the importance of understanding green consumer behaviour in order to develop better segmentation and targeting strategies is highlighted. Green consumers are changing significantly. Consumers, although with some reluctance, are moving to greener products. The Mintel organization reported that the number of consumers buying green has tripled in recent years. Furthermore, it found that the number of consumers that never bought green products have decreased. These results show that widespread environmental awareness had an important role in purchasing behaviour, with more consumers considering the environmental impact of their buying decisions and looking for a greener alternative to their conventional purchasing options. The existing literature suggests that previous research regarding the green consumer profile has different perspectives. The first group of researchers attempted to characterize green consumer profile using sociodemographic variables such as age, gender, education, income and occupation. In tum, the second group of researchers used psychographic variables instead of sociodemographic ones (Mainieri, Barnett, Valdero, Unipan, & Oskamp. Journal of Social Psychology, 137(2), 189-204, 1997). This chapter aims to better explore the importance of green consumer segmentation and its implications from a management point of view. More specifically, the aim is to analyze which variables better characterize green consumers (sociodemographic and psychographic). At the end, a theoretical framework is proposed to enable and support organizations to better understand green consumer profile. It also enables managers and marketers to target and develop better marketing strategies for these segments.